An evaluation of the characteristics and outcomes of users of a street triage service: retrospective case note review - Molodynski, A; Hollingsworth, S; Penzenstadler, L; Perfect, D; Puntis, S (Cambridge University Press, 2019)
Aims and method Street triage services are now common but the population they serve is poorly understood. We aimed to evaluate a local service to determine the characteristics of those using it and their outcomes in the 90 day period following contact.